Unexpectedly detected air bubbles in left ventricle during off-pump coronary artery bypass grafting: a case report - Youna Sim; Boohwi Hong; Sang jun Park; Man-Shik Shim (Journal of Cardiothoracic Surgery)
Abstract Background Unlike on-pump beating coronary artery bypass grafting, off-pump coronary artery bypass grafting (OPCAB) rarely causes intracardiac air embolisms. However, there have been several reports of air embolisms that occurred during OPCAB using a CO2 blower, which is commonly used to facilitate visualization of the anastomotic site. Herein, we describe a rare case of air bubbles detected only in the left ventricle during OPCAB. Case presentation A 72-year-old man visited our hospital due to a myocardial infarction. Because of diffuse tight stenosis of the coronary artery, urgent OPCAB was performed under median sternotomy. After successful grafting, a significant number of air bubbles were detected in the left ventricle but not in the right side of the heart. To prevent air embolism, the patient was maintained in the Trendelenburg position. The surgery was completed, and no neurological abnormalities were observed during hospitalization. Conclusions Air bubbles entered the left ventricle through a specific route. The use of an excessive flow rate of CO2 blower should be avoided during anastomosis. This case and other similar incidents encourage maintaining vigilant monitoring for air bubbles using transoesophageal echocardiography, even during OPCAB.